2022
DOI: 10.3389/fmicb.2022.1049979
|View full text |Cite
|
Sign up to set email alerts
|

Mouse adaptation of H6 avian influenza viruses and their molecular characteristics

Abstract: H6 avian influenza viruses (AIVs) not only continue to circulate in both domestic poultry and wild waterfowl, but also have occasionally caused spillovers infections in pigs and humans, posing a potential threat to public health. However, the molecular mechanism of H6 AIV adaptation to mammals remains largely unknown. In this study, two mouse-adapted (MA) H6 AIV strains, named as MA E-Teal/417 and MA GWF-Goose/740, were generated through blind passages in BALB/c mice. The two MA H6 strains replicated more effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that MA E-Teal/417 mainly binds to α-2.3 sialic acid (SA) ( 18 ). To determine whether amino acid substitutions of the escape mutants alter the viral receptor-binding preference, the escape mutants, m1A5 (targeting residue 69), m2C5 (targeting residue 149), m3B9 (targeting residue 139), m4C2 (targeting residue 140), m4B8 (targeting residues 120, 124, and 246), m611 (targeting residues 69 and 221), m6E3 (targeting residue 89), were tested with two receptor analogs, i.e., Neu5Acα2–3Galb1-4GlcNAcb (3′SLN) and Neu5Acα2–6Galb 1–4GlcNAcb (6′SLN), for receptor-binding preference.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that MA E-Teal/417 mainly binds to α-2.3 sialic acid (SA) ( 18 ). To determine whether amino acid substitutions of the escape mutants alter the viral receptor-binding preference, the escape mutants, m1A5 (targeting residue 69), m2C5 (targeting residue 149), m3B9 (targeting residue 139), m4C2 (targeting residue 140), m4B8 (targeting residues 120, 124, and 246), m611 (targeting residues 69 and 221), m6E3 (targeting residue 89), were tested with two receptor analogs, i.e., Neu5Acα2–3Galb1-4GlcNAcb (3′SLN) and Neu5Acα2–6Galb 1–4GlcNAcb (6′SLN), for receptor-binding preference.…”
Section: Resultsmentioning
confidence: 99%
“…The virus MA E-Teal/417 used for selection of escape mutants was generated through adaptation of E-Teal/417 in BALB/c mice ( 18 ). Compared with wild-type E-Teal/417, MA E-Teal/417 has the G124R mutation in HA ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations